2006
DOI: 10.1124/jpet.106.115758
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of the Peroxisome Proliferator-Activated Receptor δ-Selective Agonists in Vitro and in Vivo

Abstract: Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear receptor superfamily and function as ligandmodulated transcription factors that regulate gene expression in many important biological processes. The PPAR␦ subtype has the highest expression in the brain and is postulated to play a major role in neuronal cell function; however, the precise physiological roles of this receptor remain to be elucidated. Herein, we show that the high-affinity PPAR␦ agonists L-165041 [4-[3-(4-acetyl-3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 36 publications
5
132
3
Order By: Relevance
“…The beneficial role of PPAR / in stroke has been demonstrated by two different studies in which PPAR / knockout mice subjected to cerebral IRI showed significantly larger infarct size than wild-type littermates (Pialat, Cho et al 2007). This finding is confirmed by another study demonstrating that intracerebroventricular administration of high affinity PPAR / agonists such as L-165041 and GW501516 significantly decreased the infarct volume at 24 h of reperfusion after cerebral ischemia in rats (Iwashita, Muramatsu et al 2007). …”
Section: Ppars and Cerebral Ischemia 41 Experimental Data On The Effsupporting
confidence: 76%
“…The beneficial role of PPAR / in stroke has been demonstrated by two different studies in which PPAR / knockout mice subjected to cerebral IRI showed significantly larger infarct size than wild-type littermates (Pialat, Cho et al 2007). This finding is confirmed by another study demonstrating that intracerebroventricular administration of high affinity PPAR / agonists such as L-165041 and GW501516 significantly decreased the infarct volume at 24 h of reperfusion after cerebral ischemia in rats (Iwashita, Muramatsu et al 2007). …”
Section: Ppars and Cerebral Ischemia 41 Experimental Data On The Effsupporting
confidence: 76%
“…In cultured cardiomyocytes, PPAR-delta/beta agonist GW0742 inhibited LPS-induced TNF-alpha secretion, while the absence of PPAR-delta/beta further increased TNF-alpha secretion (109). Intracerebroventricular administration of high affinity PPAR-delta/beta agonists such as L-165041 and GW501516 significantly decreased the infarct volume at 24h of reperfusion after cerebral ischemia in rats (110). Furthermore, PPAR-delta/beta agonists prevented the loss of striatal dopamine after MPTP administration, suggesting that PPAR-delta/beta could serve as a potential therapeutic target in several CNS diseases (110).…”
Section: Ppar-alpha and Ppar-delta/beta Agonist-induced Neuroprotectionmentioning
confidence: 99%
“…Despite its relative novelty, several reports have already indicated neuroprotective effects of PPAR-delta in models of Alzheimer's disease [95], stroke [96,97], and Parkinson's disease [96].…”
Section: Neuroprotective Effects Of Ppardelta Agonistsmentioning
confidence: 99%